TET2 promotor methylation and TET2 protein expression in pediatric posterior fossa ependymoma. Issue 2 (28th November 2019) - Pierscianek, Daniela; Teuber‐Hanselmann, Sarah; Ahmadipour, Yahya; Darkwah Oppong, Marvin; Unteroberdörster, Meike; Müller, Oliver; Jabbarli, Ramazan; Sure, Ulrich; Zhu, Yuan; El Hindy, Nicolai
Abstract : Pediatric posterior fossa ependymoma (PF) is one of the most common brain tumors in children. Recently, two subtypes of PF were identified. PF‐A has a dismal prognosis and shows a hypermethylation phenotype, whereas PF‐B shows a great genomic instability. The ten‐eleven translocation methylcytosine dioxygenase 2 (TET2) gene ( TET2 ) has been linked to the regulation of DNA methylation. We analyzed TET2 promotor methylation and protein expression to assess the role of TET2 in PF. Medical records of all PF cases treated in our institution between 1993 and 2015 were evaluated regarding tumor histology, grade, tumor location, gender, age, tumor recurrence, distant metastasis, survival and time to progression. Subsequently, we analyzed TET2 promotor methylation using methylation‐specific polymerase chain reaction. TET2 protein expression was assessed using immunohistochemistry. Low TET2 expression was detected in seven of 17 cases. There was an association between low TET2 expression and tumor recurrence ( P = 0.049). A TET2 promotor methylation was detected in five of 10 cases. There was no association between the TET2 promotor methylation with recurrence, tumor grade or gender. TET2 promotor methylation and low TET2 expression was detected in a subgroup of PF. Our data show an association between low TET2 expression and tumor recurrence in PF.